PLANTAS DE COBERTURA E SEU EFEITO SOBRE OS TEORES DE CARBONO E NITROGÊNIO DO SOLO - BERGAMACO, Amanda; LIMA, Isabela Machado de Oliveira; SILVA, Maiara Fernanda Garcia; BARBOSA, Giselle Feliciani; ENSINAS, Simone Cândido (ANAIS DO ENIC, 2018)
-